Integrin overexpression induced by high glucose and by human diabetes: potential pathway to cell dysfunction in diabetic microangiopathy. - Roth, T (1993)
The nature of the process leading to the acellular nonperfused capillaries of diabetic microangiopathy remains unknown. Because these capillaries manifest thickened basement membranes, we asked whether the process causing deposition of excess extracellular matrix in diabetes modifies cell-matrix interactions in a direction that would compromise cell renewal. In 44 individual isolates of human umbilical vein endothelial cells we observed that high glucose concentrations (30 mM) induce coordinate increases in the levels of mRNAs encoding fibronectin and the fibronectin-specific integrin receptor alpha 5 beta 1 as well as in the cognate proteins. Expression of the integrin subunit alpha 3, component of the alpha 3 beta 1 polyspecific receptor for fibronectin, laminin, and collagen, was also up-regulated by high glucose. Overexpression of integrins correlated with increased cell attachment to exogenous fibronectin and laminin as well as to complex matrix. Moreover, cells exhibited firmer steady-state adhesion to their own matrix. To correlate these in vitro observations with events in human diabetic retinopathy we measured integrin levels in retinal trypsin digests prepared from 10 patients with 8.2 +/- 1.6 (mean +/- SE) years of diabetes and 10 age- and sex-matched nondiabetic controls. Microvessels of diabetic patients showed increased immunostaining for beta 1 integrin (P = 0.025) when compared with control microvessels. These data show that high glucose and diabetes increase integrin expression and thus alter the interaction of vascular endothelial cells with their basement membranes in the direction of firmer cell-matrix adhesion. This could compromise the migration and replication critical to the reendothelialization process and contribute to microvascular occlusion.